QUALITY OF LIFE AT WORK (CIPEEX, 2024)
Quality of Work Life (QWL) is a concept that refers to the level of satisfaction, well-being, and fulfillment that individuals experience in their work environment. It encompasses various elements that affect workers' experiences and has a significant impact on their overall quality of life. This research aimed to assess individuals' perceptions of their quality of work life. The methodology used for the research involved collecting data by administering the QWL-Walton questionnaire via Google Forms. It was applied online through links sent via the WhatsApp application to 32 individuals from six cities in the São Patrício Valley in the state of Goiás, Brazil. Among the participants, 23 were women and 9 were men, ranging in age from 18 to 40 years, representing various fields of work. Regarding the aspect of satisfaction, the majority of respondents stated that they were satisfied with their work hours in the company, as well as with the individual and collective protective equipment provided. Satisfaction with the work hours is a significant indicator of well-being in the professional environment, suggesting that employees are comfortable with the number of hours dedicated to work, and this workload is not causing stress or burnout. Additionally, satisfaction with individual and collective protective equipment is crucial to ensuring the safety and health of workers, reducing the risk of accidents and occupational diseases, which can contribute to a healthier and more satisfying work environment. Another noteworthy result was that half of the participants reported being dissatisfied with their salaries at the company. Salary dissatisfaction can negatively impact employee motivation and engagement, affecting the quality of life in the professional environment. Therefore, organizations should carefully evaluate compensation and salary policies, seeking ways to improve employee satisfaction in this regard. The data also revealed that the majority of respondents reported having a good social relationship with their colleagues, which is a positive indicator for QWL. A good social relationship in the workplace is a fundamental component, and this positive interaction contributes to the creation of a healthy work environment and the promotion of employee well-being. In conclusion, there is a trend towards satisfaction with QWL in the workplace.